A Graph Theory approach to measure the performance of sustainability enablers in a manufacturing organization. Issue 1 (2nd January 2016) - Jayakrishna, K.; Vinodh, S.; Anish, S.
Abstract : In a manufacturing organization, the term sustainability deals with the impact of production process and products on the environment and society, laying emphasis on preservation of scarce resources. In this article, the study concentrates on developing a Graph Theory model to measure the performance and inter-relationship between the sustainability enablers in an organization, thereby to quantitatively measure the extent to which 'sustainable manufacturing' practices are being followed in the organization. The objective of this study was to identify a set of sustainability enablers and attributes that impact a manufacturing organization. Digraphs were developed for the whole system and sub-systems depicting the inter-relationships and dependencies between various enablers and attributes to interpret the performance of the sustainability enablers in the case organization. Using the best case and worst case values, the level of sustainable manufacturing practices of the organization was found by Comprehensive Assessment Index. Based on the best case values, the relative significance of individual sustainability enablers are found and compared with worst case situations. The impacts of individual enablers on the overall sustainability level of the organization were also studied.